Kaleidoscope : (McGraw-Hill, 2008)
Kaleidoscope condenses the essence of Open Court Reading in order to intensify the instruction, making it possible to deliver two years of instruction in one year. The precise, targeted lessons within Kaleidoscope provide explicit, systematic instruction in phonics, vocabulary, text comprehension, and writing. Controlled reading material is provided to assure student success Features.